Replicator dominance in a eukaryotic chromosome. - Marahrens, Y (1994)
Replicators are genetic elements that control initiation at an origin of DNA replication (ori). They were first identified in the yeast Saccharomyces cerevisiae as autonomously replicating sequences (ARSs) that confer on a plasmid the ability to replicate in the S phase of the cell cycle. The DNA sequences required for ARS function on a plasmid have been defined, but because many sequences that participate in ARS activity are not components of chromosomal replicators, a mutational analysis of the ARS1 replicator located on chromosome IV of S. cerevisiae was performed. The results of this analysis indicate that four DNA elements (A, B1, B2 and B3) are either essential or important for ori activation in the chromosome. In a yeast strain containing two closely spaced and identical copies of the ARS1 replicator in the chromosome, only one is active. The mechanism of replicator repression requires the essential A element of the active replicator. This element is the binding site for the origin recognition complex (ORC), a putative initiator protein. The process that determines which replicator is used, however, depends entirely upon flanking DNA sequences.